Violent Cinema and Children with Special Needs: Exploring the Effects of Violent Cinema on Children with Special Needs (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The following paper aims to analyse the impact of watching violent media on Children with Special Needs. It inculcates a Case Study of a Down Syndrome boy who got access to a number of violent films and videos through online and offline media. It is followed by an analysis of behavioural changes that are observed with the help of a professional Special Educator. The paper also includes a personal interview of the aforementioned expert in the field. A detailed analysis is followed by the ramifications and risks possible because of the impacts. The paper concludes with a detailed and well researched compilation as well as testing of improvement techniques.